2010
DOI: 10.1097/ccm.0b013e3181f26fe6
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate consent for research involving adults with impaired decision making: Survey of Institutional Review Board practices

Abstract: Objectives Most critically ill adults have impaired decision-making capacity and are unable to consent to research. Yet, little is known about how Institutional Review Boards interpret the Common Rule’s call for safeguards in research involving incapacitated adults. We aimed to examine Institutional Review Board practices on surrogate consent and other safeguards to protect incapacitated adults in research. Design, Settings, and Participants A cross-sectional survey of 104 Institutional Review Boards from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…Gong et al 10 reported that when presented with a hypothetical genetic epidemiology study involving incapacitated patients, most IRB members reported that such a study would represent greater than minimal risk, and 40% would not allow such a study to proceed in the absence of direct patient benefit. Similarly, in a multicenter genetic epidemiology acute stroke study, Chen et al 11 reported that investigators preferentially enrolled less severely affected, cognitively intact participants because IRBs at 40% of participating institutions would not permit use of SDMs to provide consent in this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gong et al 10 reported that when presented with a hypothetical genetic epidemiology study involving incapacitated patients, most IRB members reported that such a study would represent greater than minimal risk, and 40% would not allow such a study to proceed in the absence of direct patient benefit. Similarly, in a multicenter genetic epidemiology acute stroke study, Chen et al 11 reported that investigators preferentially enrolled less severely affected, cognitively intact participants because IRBs at 40% of participating institutions would not permit use of SDMs to provide consent in this context.…”
Section: Discussionmentioning
confidence: 99%
“…6 Investigations involving cognitively impaired individuals are perceived as carrying greater risk and requiring additional safeguards as compared with studies enrolling those who are cognitively intact. 10 When these studies entail collection of genetic material, such concerns appear heightened. 10,11 Although a number of investigations have examined attitudes regarding gene variation research, the manner in which the exigencies of acute illness affect perceptions of genetic data collection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3–5) Despite several decades of debate in the U.S., no clear policy exists regarding the involvement of adults with decisional impairments in clinical research. (6) AD research centers(7, 8) research ethics review boards(9, 10), and dementia experts and advocates(11) vary considerably in their viewpoints, policies and practices in dealing with this ethical issue.…”
mentioning
confidence: 99%
“…To ensure that science and knowledge can continue to advance while respecting the ethical principle of autonomy, we commonly asked substitute decision-makers (SDMs) to provide consent on patients' behalf [1,2]. In situations where a study is deemed to pose only minimal risk, for example, observational studies, some research ethics boards may waive the need for informed consent, although the criteria used to establish minimal risk have varied [3,4]. Studying interventions that must be administered on an emergency basis can further complicate the informed consent process due to the inability to identify SDMs within a suitable time frame [5].…”
mentioning
confidence: 99%